5E FACTOR: THE MAJOR CONTRIBUTING FACTORS IN LEARNING SECOND LANGUAGE - Srivastava, Sarika; Batra, Jagdish (International Journal For Research In Business, Management And Accounting, 2019)
In a current scenario to succeed in life one should know at least three languages; the mother tongue, the national and an international language, as English enjoys the status of associate official language at an international level, In last few years we have witnessed the increased need for an English-proficient workforce for companies trying to grow on a global scale. And Over the time companies will require more people to speak English and thus this will drive a bigger focus on English proficiency in education, both at the higher level and among young learners. So to meet the future demand, we have to prepare our budding aspirants accordingly. This paper aims to highlight the 5E’ factors which has a major affect on learning Second language and an effort is to find out some solid solution to those problems.